1970
DOI: 10.3126/jcmsn.v6i2.3610
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing indicators and pattern of use of antibiotics among medical outpatients in a teaching hospital of Central Nepal

Abstract: The study of prescriptions using prescribing indicators enables us to detect some common problems of prescribing and to focus subsequent efforts to correct them. This study was designed to define the extent and pattern of drug prescribing with emphasis on that of antibiotics among medical outpatients of teaching hospital of College of Medical Sciences Bharatpur, Nepal. The data contained on randomly selected original prescriptions of patients attending medical OPD in between January2008 and June2008 were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 10 publications
3
18
0
2
Order By: Relevance
“…12 The mean of antibiotics prescribed from NLEM of India showed that not all the antimicrobials included from the NLEM of India. A mono drug prescription in the retrospective study was found to be consistent with the study conducted in Nepal 15 and the WHO guidelines. [17][18][19][20] The frequently of single antibiotic prescription was consistent with other studies and the WHO guidelines.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…12 The mean of antibiotics prescribed from NLEM of India showed that not all the antimicrobials included from the NLEM of India. A mono drug prescription in the retrospective study was found to be consistent with the study conducted in Nepal 15 and the WHO guidelines. [17][18][19][20] The frequently of single antibiotic prescription was consistent with other studies and the WHO guidelines.…”
Section: Discussionsupporting
confidence: 69%
“…This result was consistent with the study conducted in Italy. 15 The majority of common childhood illnesses are caused by viruses which do not require antibiotics. The proportion of antibiotic prescription was 79.4% in the present study as against the WHO recommendation of 20% antibiotic use for these common childhood illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prescribing was rational, it was felt that an inclination towards branded products and an over use of antibiotics were prevalent. The need of an educational intervention, as well as a strict antibiotic policy was felt [10]. Developing and maintaining an electronic documentation of the patients' medical records may serve as a valuable tool for auditing the prescriptions frequently and for implementing the antibiotic policy.…”
Section: Attitudementioning
confidence: 99%
“…Although the selections of the antibiotics were rational, bacteriological confirmations prior to the institution of antibiotics, were not done in any case. The inclination towards the use of branded products and the overuse of antibiotics were revealed as the problems which required educational interventions and a strict antibiotic policy [10].…”
Section: Attitudementioning
confidence: 99%
See 1 more Smart Citation